Fe2Si5N8: Access to Open‐Shell Transition‐Metal Nitridosilicates. (6th February 2018) - Bielec, Philipp; Janka, Oliver; Block, Theresa; Pöttgen, Rainer; Schnick, Wolfgang
Abstract: Highly condensed nitridosilicates doped with Eu 2+ or Ce 3+ play an important role in saving energy by converting the blue light of (In, Ga)N‐LEDs. Although nitridosilicates are known for great structural variety based on covalent anionic Si‐N networks, elemental variety is restricted. Presenting a significant extension of the latter, this work describes a general access to open‐shell transition‐metal nitridosilicates. As a proof‐of‐principle, the first iron nitridosilicate, namely Fe2 Si5 N8, was prepared by exchanging Ca 2+ in α‐Ca2 Si5 N8 applying a FeCl2 melt (salt metathesis). The title compound was analyzed by powder X‐ray diffraction, EDX, ICP‐OES, combustion analysis, TG/DSC, Mössbauer spectroscopy and magnetic susceptibility measurements. Furthermore, the structure of α‐Ca2 Si5 N8 was determined at 1073 and 1173 K confirming the anionic network of α‐Ca2 Si5 N8 providing possible migration pathways for the ion‐exchange reaction.